2019
DOI: 10.3390/fib7040035
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Development of Polymer Blend Fibers along Spinning Line

Abstract: Melt spinning is an efficient platform to continuously produce fiber materials with multifunctional and novel properties at a large scale. This paper briefly reviews research works that reveal the morphology development of immiscible polymer blend fibers during melt spinning. The better understanding of the formation and development of morphology of polymer blend fibers during melt spinning could help us to generate desired morphologies and precisely control the final properties of fiber materials via the melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Developing polymer binary systems is a versatile strategy for obtaining novel biomaterials with improved properties [101,102]. The addition of the second polymer in a binary system not only provides the original characteristics of the additives to the polymer blend, but also generates novel attributes by tuning the structure of the polymer blend, improving processing and lowering production costs [103][104][105]. To fabricate functional materials, such as biomaterials using binary polymer fibres, forming must occur on a technologically viable scale, generating fibres with a large surface area and tuneable porosity [38,106].…”
Section: Fibre Production Techniques Relevant To Binary Polymer Systemsmentioning
confidence: 99%
“…Developing polymer binary systems is a versatile strategy for obtaining novel biomaterials with improved properties [101,102]. The addition of the second polymer in a binary system not only provides the original characteristics of the additives to the polymer blend, but also generates novel attributes by tuning the structure of the polymer blend, improving processing and lowering production costs [103][104][105]. To fabricate functional materials, such as biomaterials using binary polymer fibres, forming must occur on a technologically viable scale, generating fibres with a large surface area and tuneable porosity [38,106].…”
Section: Fibre Production Techniques Relevant To Binary Polymer Systemsmentioning
confidence: 99%
“…Another fundamental factor influencing the development of the phase morphology during melt processing operation dominated by the elongational flow is coalescence; in fact, in the presence of intense interactions among the particles of dispersed phase, due to high concentration or restricted geometries, numerous collisions occur, hence possibly causing coalescence phenomena [159]. For instance, during melt spinning, the shrinking matrix compresses the droplets of dispersed phase, enabling them to migrate form the surface toward the center of the fiber and promoting coalescence events [160,161]. He et al [162] reported the formation of a coalescence region during the melt spinning of immiscible polystyrene/polypropylene blends performed at take-up rates higher than 750 m/min, in which an increase of the diameter of the droplets of polystyrene along the spinning line was observed.…”
Section: Morphology Evolution Of Polymer-based Blends Under Elongational Flowmentioning
confidence: 99%
“…Thermoplastic polymers are environmentally friendly, and it can improve impact strength, damage tolerance, durability, and repair capability. However, the relatively high viscosity (100-10,000 Pa.s) of molten thermoplastics limits the impregnation capability, resulting in poor product quality (Chen et al, 2019;Zoller et al, 2019).…”
Section: Fig 3 -Illustration Of Pultrusion Processmentioning
confidence: 99%